Evidence of ongoing radial migration in NGC 6754: azimuthal variations of the gas properties - Sánchez-Menguiano, Laura; Grand, Robert J. J. (Arxiv, 2016)
Understanding the nature of spiral structure in disk galaxies is one of the main, and still unsolved questions in galactic astronomy. However, theoretical works are proposing new testable predictions whose detection is becoming feasible with recent development in instrumentation. In particular, streaming motions along spiral arms are expected to induce azimuthal variations in the chemical composition of a galaxy at a given galactic radius. In this letter we analyse the gas content in NGC 6754 with VLT/MUSE data to characterise its 2D chemical composition and H$α$ line-of-sight velocity distribution. We find that the trailing (leading) edge of the NGC 6754 spiral arms show signatures of tangentially-slower, radially-outward (tangentially-faster, radially-inward) streaming motions of metal-rich (poor) gas over a large range of radii. These results show direct evidence of gas radial migration for the first time. We compare our results with the gas behaviour in a $N$-body disk simulation showing spiral morphological features rotating with a similar speed as the gas at every radius, in good agreement with the observed trend. This indicates that the spiral arm features in NGC 6754 may be transient and rotate similarly as the gas does at a large range of radii.